Examining the Role of Career Development Initiative on Work Engagement in Nepalese Commercial Banks - Kharel, Shreekrishna; Niraula, Ganesh Prasad (KIC International Journal of Social Science and Management, 2024)
The highly committed and enthusiastic employees are crucial for the development of an organization and its wellbeing. This study aims to examine the relationship between career development initiative and work engagement. This study employs cross-sectional research design and positivist epistemology. Data were collected from 250 banks employees working in 10 commercial banks across the country. The stratified random sampling was used. A standardized Likert scale was used to collect the data with 1 denoting strongly disagree and 5 denoting strongly agree. The Statistical Package for Social Science was used to analyze the data and proposed hypothesized relationships. The findings reveal that training and development is positively and significantly associated with work engagement. Similarly, managerial coaching is positively and significantly associated with work engagement. Additionally, talent management is positively and significantly associated with work engagement. Existing literature has examined the impact of career development initiative and work engagement. However, empirical research investigating the relationship among different organizational characteristics and work engagement remains limited. Therefore, the bank managers and policy makers can leverage the findings of this research as a strategic tool for developing organizational policies aimed to foster work engagement.